An X‐linked syndrome with severe neurodevelopmental delay, hydrocephalus, and early lethality caused by a missense variation in the OTUD5 gene. Issue 2 (9th November 2020) - Tripolszki, Kornelia; Sasaki, Erina; Hotakainen, Ronja; Kassim, Abdul Halim; Pereira, Catarina; Rolfs, Arndt; Bauer, Peter; Reardon, William; Bertoli‐Avella, Aida M.
Abstract: We describe an X‐linked syndrome in 13 male patients from a single family with three generations affected. Patients presented prenatally or during the neonatal period with intrauterine growth retardation, ventriculomegaly, hydrocephalus, hypotonia, congenital heart defects, hypospadias, and severe neurodevelopmental delay. The disease is typically fatal during infancy, mainly due to sepsis (pneumonias). Female carriers are asymptomatic. We performed genome sequencing in four individuals and identified a unique candidate variant in the OTUD5 gene (NM_017602.3:c.598G > A, p.Glu200Lys). The variant cosegregated with the disease in 10 tested individuals. OTUD5 was considered as a candidate gene based on two previous missense variants detected in patients with intellectual disability. In conclusion, we define a syndrome associated with OTUD 5 defects and add compelling evidence of genotype–phenotype association. This finding ended the long diagnostic odyssey of this family. Abstract :